2007
DOI: 10.1111/j.1600-0714.1998.tb01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Spindle cell carcinoma of the gingiva: report of an autopsy case

Abstract: An autopsied case of an 80‐year‐old man with spindle cell carcinoma of the gingiva is reported. The tumor was polypoid and mostly composed of a sarcomatous proliferation of spindle cells with a small focus of squamous cell carcinoma at the stalk portion. The carcinoma metastasized to a cervical lymph node, lungs and pleura with extension to the diaphragm. In the metastatic lymph node, the squamous cell component was more prominent than the spindle cell one, while only anaplastic pleomorphic carcinoma cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…The presence of junctional complexes between tumor cells, with or without pericellular basal lamina and cytoplasmic skeins of intermediate filament has been demonstrated [20]. It has been suggested that development of the spindle cell phenotype involves functional loss of genes that control epithelial differentiation and that conversion to spindle morphology is a recessive entry [21]. It has been documented that keratin proteins may be regarded as molecular markers for stratified squamous epithelial cells in normal tissues and in neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of junctional complexes between tumor cells, with or without pericellular basal lamina and cytoplasmic skeins of intermediate filament has been demonstrated [20]. It has been suggested that development of the spindle cell phenotype involves functional loss of genes that control epithelial differentiation and that conversion to spindle morphology is a recessive entry [21]. It has been documented that keratin proteins may be regarded as molecular markers for stratified squamous epithelial cells in normal tissues and in neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of mesenchymal metaplasia within the tumor may vary widely and may be seen as bony or cartilagenous elements within the tumor or as aberrant immunohistochemical marker expression [2][3][4][5][6][7][8][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Although no aberrant metaplastic elements were observed in any of our cases, we did see aberrant expression of vimentin, calponin, SMA, desmin and S100 protein, which is also well reported in literature [3].…”
Section: Histomorphologymentioning
confidence: 99%
“…Sarcomatoid (spindle cell) carcinomas of the head and neck are unusual variants of squamous carcinoma commonly reported in the larynx but also described in other mucosal sites such as gingiva, tongue, hypopharynx and nasal cavity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. These tumors have now been proved to be monoclonal, evolving from conventional squamous carcinoma with dedifferentiation associated with sarcomatoid transformation [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…A tumor of the oral cavity and oropharynx is potentially aggressive and seems recur easily and to metastasize easily 9 . The incidence of metastases was 36% and the 2-year survival rate was 55% in tumors involving the oral cavity 1 .…”
Section: ⅲ Discussionmentioning
confidence: 97%
“…It is a unique variant of squamous cell carcinoma consisting of sarcomatoid proliferation of plemorphic spindle-shaped cells sometimes with a biphasic appearance presenting as a part of frank squamous cell carcinoma 1,2 . This type of carcinoma has been described using various terms, including spindle cell squamous carcinoma, carcinosarcoma, pseudosarcoma, and pleomorphic carcinoma1.…”
Section: ⅰ Introductionmentioning
confidence: 99%